Oviduct Patency Control by Means of 133Xe-Solution - Pertyński, T.; Radecki, W.; Bialobrzeski, J. (Nuklearmedizin - NuclearMedicine, 1976)
The authors describe a radioisotopic method for the oviduct patency control in patients suffering from primary or secondary sterility. The application of 133Xe causes at least about 3—4 times less radiation than hysterosalpingographical tests.Ease of interpretation facility, painlessness and comparability of the results were noticed.